Kinetics of Ion Exchange Resin Amberlite IRA 400 - Lokhande, R.S.; U. Singare, Pravin (Asian Journal of Chemistry, 2010)
131l has been employed as a tracer to study kinetics of first orderreaction. The study was carried for different concentrations of KIsolution [electrolyte], different temperatures and different amountsof ion exchange resins. Reaction rates were calculated by using firstorder reaction rate equation. From the reaction rates the energy ofactivation was calculated. The energy of activation was found todecrease with increase in concentration of the electrolyte. For concentrationof 0.0025 KI solution, energy of activation is found tobe 4.95 kJ/mole which decreases to 4.08 kl/mole for 0.020 Msolution.